2011
DOI: 10.1002/jpln.201000004
|View full text |Cite
|
Sign up to set email alerts
|

Species‐specific differences in nitrogen uptake and utilization by six European tree species

Abstract: Species‐specific uptake and allocation mechanisms for N are scarce, in particular when trees are cultivated in potted soil under more natural conditions than in hydroponic culture. The objective of this study was to compare specific N‐uptake rates for economically and ecologically important tree species in Central European forests: pine (Pinus sylvestris), spruce (Picea abies), oak (Quercus petraea), beech (Fagus sylvatica), lime (Tilia cordata), and ash (Fraxinus excelsior) when they grow in mineral soil from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 29 publications
1
27
2
1
Order By: Relevance
“…These values were within the range of previous reports (Eddy et al 2008;Uscola et al 2017), although the experimental conditions varied. Our results suggest that low fine root biomass but high specific N-uptake rate, which maximizes whole-plant growth rates (Osone and Tateno, 2005;Schulz et al 2011), would contribute to the suppression of N loss on Oxisols. In contrast, plants on Ultisols would invest more in root formation in the O horizon to capture N before leaching down to the mineral horizon.…”
Section: Roles and Controls On Fine Rootsmentioning
confidence: 78%
“…These values were within the range of previous reports (Eddy et al 2008;Uscola et al 2017), although the experimental conditions varied. Our results suggest that low fine root biomass but high specific N-uptake rate, which maximizes whole-plant growth rates (Osone and Tateno, 2005;Schulz et al 2011), would contribute to the suppression of N loss on Oxisols. In contrast, plants on Ultisols would invest more in root formation in the O horizon to capture N before leaching down to the mineral horizon.…”
Section: Roles and Controls On Fine Rootsmentioning
confidence: 78%
“…). As fits with a nitrophilous species, Schulz, Härtling & Stange () found that the N uptake of 2‐year‐old seedlings was greatest in ash ( F. excelsior > Tilia cordata > Pinus sylvestris > Picea abies > Fagus sylvatica > Quercus petraea ) although relative growth rate in ash was similar to the other species (0.375 g fresh mass day −1 in ash). Ash can react well to fertilizers on poor soils (Bulíř ), but they have little effect on already rich soils (Culleton, Murphy & McLoughlin ).…”
Section: Structure and Physiologymentioning
confidence: 88%
“…N uptake is calculated on an annual time step as Nuptake(t)=Nmin(1exp(krBr(t))), where k r (m 2 g −1 C) is a species trait that describes root N uptake efficiency (analogous to the light extinction coefficient). An increase in the value of k r increases the N uptake per unit root biomass (Zerihun & Bassirirad ; Schulze, Härtling & Stange ).…”
Section: Methodsmentioning
confidence: 99%